Control and documentation studies of the impact of blasting on buildings in the surroundings of open pit mines - Anna Sołtys; Michał Twardosz; Jan Winzer (Journal of Sustainable Mining, 2017)
Environmental Protection Law together with Geological and Mining Law impose on a mining plant a duty to protect its surroundings against the effects of mining operations. It also refers to the impact of vibrations on people and buildings induced by blasting works. Effective protection is possible only if the actual level of the impact is known, hence it has to be recorded. It was and still is the keynote idea of the research conducted at the AGH Laboratory of Blasting and Environmental Protection. The effect of many years of research is the development of an original and, in particular, an effective procedure to record the impact of blasting works with periodical measurements of vibration intensity or monitoring the vibrations' impact on buildings in the surrounding area. These assumptions form part of preventive actions taken by open pit mines, which are aimed at minimizing the impact of blast workings on the surroundings and are often recommended by experts. This article presents the course of action concerning control tests of vibration intensity in the surroundings of a mine. It also shows it is necessary to monitor vibrations in buildings as it is a source of knowledge for the mining plant management personnel and engineers who conduct blasting works, thus contributing to an increase in awareness of the responsible management of a mining plant. The Vibration Monitoring Station (KSMD) developed by a research group, after several upgrades, has become a fully automated system for monitoring and recording the impact of blast workings on the surroundings. Moreover, it should be emphasised that without the mine management personnel's cooperation, it would be impossible to work and achieve the common goal, i.e. conducting blasting works in a way that is safe for the surroundings.